South-South Economic Linkages: An Overview - Shikha Jha; Peter McCawley (Asian Development Bank (ADB), 2011)
The nature of South–South international economic relations has changed significantly in recent decades, especially since the early 1990s. In areas such as trade, investment, labor markets, technology, and policy coordination, regional cooperation between countries of the South and pro-market policies have supported a rapid growth in South–South linkages. Looking ahead, the prospects are that the changing architecture of international economic relations that South–South cooperation has underpinned will contribute to growth across the developing world. Governments in developing countries of the Asia and Pacific region can foster expanded South–South cooperation by strengthening the capacity of governments to support pro-market policies. Potential gains for the region include expanded opportunities to promote growth and productivity, openings to expand connectivity between and within countries, a stronger collective voice in global decision making, more effective regional institutions, and improved economic security and stability.
hdl:11540/2016
Keywords: F02; F15; F21; F22; F42; F55; O19; 330; South-South economic linkages; trade; investment; labor markets; policy coordination; regional cooperation; Internationale Wirtschaftsbeziehungen; Handelsliberalisierung; Finanzmarktregulierung; Süd-Süd-Beziehungen; Weltwirtschaftsordnung; Asiatisch-pazifischer Raum; Welt